RISE of the HAIRY HORROR - Gray, Kes; Parsons, Garry (London : Red Fox, 2017)
The second brilliant book in the Jack Beechwhistle series. The world's a dangerous place. Luckily, Jack Beechwhistle is around to protect it. He might look like an ordinary boy, but really he's a junior secret agent. He's tackled all sorts of missions - exploding conkers, zombie sweet-shop owners, and man-eating giant slugs - with a bit of help from his best friends and sidekicks, Colin and Harry (as long as it's not past their bedtime). Then Jack notices something strange and suspicious about the hairdresser in town, Valentino. Every time Valentino cuts someone's hair, he sweeps the hairs up and collects them in a big plastic bag. But what is he using them for?Everything points to Valentino being an evil enemy agent! And Jack Beechwhistle's on the case ...
Keywords: Heroes -- Juvenile fiction; Hairdressing -- Juvenile fiction; Heroes -- Juvenile fiction; Boys -- Juvenile fiction; Humorous fiction; Children's stories